Measurement Of Ethanol Concentration in Liquid Organic Fertilizer Fermentation Emissions Using The MQ-8 Sensor - Safitri, Dewi Ayu; Wardoyo, Arinto Yudi Ponco; Istiroyah; Adi, Eko Teguh Purwito (Master Program in Mechanical Engineering, Gunadarma University, 2024)
Ethanol is beneficial for the sterilization process and increases the rate of photosynthesis. Measurement of ethanol concentration is necessary because ethanol in high concentrations can cause several health problems, such as eye irritation, coughing, lacerations, and ineffective plant sterilization processes. Therefore, a sensor-based measurement system is needed to measure the total gas concentration in liquid organic fertilizer. This research aims to characterize the MQ-8 sensor and analyze the ethanol concentration for the fermentation process. The results of this study indicate that the MQ-8 sensor can work well in measuring the concentration of a single ethanol compound with an accuracy of 91%. The total concentration of ethanol gas in each sample liquid organic fertilizer is measured between 216 ppm to 1583 ppm, depending on the fermented plant.